Принципи забезпечення цивільного захисту на регіональному рівні - Остап'юк, А. Ю.; Ostapiuk, A. Yu. (Вісник Пенітенціарної асоціації України. - 2023. - № 4(26). - С. 42-48, 2023)
Стаття присвячена дослідженню принципів забезпечення цивільного захисту на регіональному рівні, які визначено як сукупність вихідних основ, базових ідей, які визначають порядок правового регулювання, а також організації та практичної реалізації заходів цивільного захисту на території певного регіону. Відмічено, що законність – це основоположна ідея забезпечення цивільного захисту на регіональному рівні. Аргументовано, що окрім законності, до принципів забезпечення цивільного захисту на територіальному рівні також доцільно віднести наступні принципи: системності та безперервності; рівності та одноманітності забезпечення цивільного захисту в межах території регіону; партнерства суб’єктів забезпечення публічної безпеки та порядку; еволюційності; науковості.

It was concluded that the principles of providing civil protection at the regional level are a set of basic principles, basic ideas that determine the order of legal regulation, as well as the organization and practical implementation of civil protection measures on the territory of a certain region. It was noted that legality, as the fundamental idea of civil protection at the regional level, is expressed in: first, strict and unconditional compliance of the civil protection process within a specific region, based on the provisions of legislative, by-law and local regulatory acts; secondly, the activities of civil protection entities exclusively within the framework of the rights and obligations assigned to them by the norms of current legislation; thirdly, the responsibility of these subjects for violations and miscalculations in the implementation of relevant measures It is argued that, in addition to legality, the principles of providing civil protection at the territorial level should also include the following: the principle of systematicity and continuity; the principle of equality and uniformity of providing civil protection within the territory of the region; the principle of partnership of subjects ensuring public safety and order; principle of evolution; the principle of scientificity. As a conclusion of the presented scientific research, the author makes a generalization that the above principles are not only the ideological basis of the functioning of the institute considered in the article, they also form vectors for the further development of civil protection at the regional level. The scientific novelty of the article lies in the fact that the theoretical approach regarding the list and content of the key principles of ensuring civil protection at the regional level was further elaborated in the work.

Статья посвящена исследованию принципов обеспечения гражданской защиты на региональном уровне, определенных как совокупность исходных основ, базовых идей, определяющих порядок правового регулирования, а также организации и практической реализации мер гражданской защиты на территории определенного региона. Отмечено, что законность – это основополагающая идея обеспечения гражданской защиты на региональном уровне. Аргументировано, что кроме законности к принципам обеспечения гражданской защиты на территориальном уровне также целесообразно отнести следующие принципы: системности и непрерывности; равенства и единообразия обеспечения гражданской защиты внутри территории региона; партнерства субъектов обеспечения публичной безопасности и порядка; эволюционности; научности.
Principles of providing civil protection at the regional level
Keywords: принципи; принципи права; забезпечення; цивільний захист; регіональний рівень; principles; principles of law; security; civil protection; regional level; принципы; принципы права; обеспечение; гражданская защита; региональный уровень